Nanomaterials for Fuel Cell Catalysis - Ozoemena, Kenneth I.; Chen, Shaowei (Nanostructure Science and Technology, 2016)
Global experts provide an authoritative source of information on the use of electrochemical fuel cells, and in particular discuss the use of nanomaterials to enhance the performance of existing energy systems. The book covers the state of the art in the design, preparation, and engineering of nanoscale functional materials as effective catalysts for fuel cell chemistry, highlights recent progress in electrocatalysis at both fuel cell anode and cathode, and details perspectives and challenges in future research.